We are here with you hands in hands to facilitate your learning & don't appreciate the idea of copying or replicating solutions. Read More>>
MTH100 GDB Solution & Discussion Last Date:13-12-2016
Find the sum of the geometric series to 7th term by using formula for finding sum of geometric series.
If you successfully able to find the common ratio, then 25% marks will be awarded.
If you will write the correct formula for finding sum, then you will be awarded 50% marks.
Inserting correct values in formula, will give you 75% marks.
Find the correct sum will give you 100% marks.
.+ http://bit.ly/vucodes (Link for Assignments, GDBs & Online Quizzes Solution)
+ http://bit.ly/papersvu (Link for Past Papers, Solved MCQs, Short Notes & More)+ Click Here to Search (Looking For something at vustudents.ning.com?) + Click Here To Join (Our facebook study Group)
Please Discuss here about this GDB.Thanks
Our main purpose here discussion not just Solution
We are here with you hands in hands to facilitate your learning and do not appreciate the idea of copying or replicating solutions. Read More>>
For Important Helping Material related to this subject (Solved MCQs, Short Notes, Solved past Papers, E-Books, FAQ,Short Questions Answers & more). You must view all the featured Discussion in this subject group.
For how you can view all the Featured discussions click on the Back to Subject Name Discussions link below the title of this Discussion & then under featured Discussion corner click on the view all link.
Or visit this link
Series will be 1-2+4-8+16-32+64
Sum will be 43.
common ratio is -1/2
required in GDB
3...and answer of sum is
7 numbers of series will be
Sum of 7 numbers = 43
r means the value that is multiplied with old number to make a new number
like 1st number = 1 * -2 =-2 (2nd number)
2nd numebr = -2 * -2 =4 (3rd number
3rd number = 4 * -2 = -8 (4th number )
i mean to say that 2 is the value that is producing new series number so r= -2
a7= 1 (-2)^7-1
a7 = 2^6
a7 = 64
to find 6th value using formula , apply this formula again
common ratio sab mai same hotii hai as proved below
common ratio = -2 (if i m nt wrng)
common ratio = a2/a1 = -2/1 = -2
= a3/a2 = 4/-2 = -2
= a4/a3 = -8/4 = -2
From the question:
a1 = 1
a2 = -2
a3 = 4
n = 7
Common ratio = r
r = a2/a1 = a3/a2
r = -2/1 = 4/-2 =-2
r = -2
Now sum = Sn
Sn = a1 (1-r^n) / 1-r
S7 = 1(1-(1-(-2^7)) / 1-(-2)
S7 = 1+128 / 1+2
S7 = 129 / 3
S7 = 43
MTH100 GDB Solution